위기사건을 활용한 문화간 훈련 프로그램의 개발과 적용 - 이선미(Lee, Seon Mi) (교양교육연구, 2015)
본 연구는 단기 문화간 접촉과 병행하여 이루어지는 문화간 훈련을 통해 학생들의 문화간 역량 개발을 촉진할 수 있다는 전제에서 출발한다. 본 연구의 목적은 단기 해외 체험 프로그램 참여 예정자를 위한 문화간 훈련 프로그램을 개발하고 적용하는 것이다. 주된 훈련 방법으로 ‘위기사건(critical incidents)’ 방법을 활용했는데, 이는 타문화권에서 게스트로서 한국인이 경험하는 당혹, 오해, 문제, 갈등의 짧은 상황을 훈련 소재로 활용한다는 점에서, 학습자의 동기부여, 문제해결 중심의 역량 교육에 효과적인 방법이다. 7개 국가에 관련된 총 127개의 위기사건 사례들과 이를 활용한 3시간의 훈련 프로그램을 개발하였고, 이를 서울여대 해외 체험 프로그램 참여자를 위한 사전교육의 형식으로 적용하였다. 훈련 프로그램 적용 결과, 학생들은 목적 국가에 대한 편견과 판단을 잠정적으로 유보하고 한국 문화와 다른 문화를 모두 상대화하여 볼 수 있는 관점을 가지게 되었으며, 문화간 접촉에서 생기는 갈등과 혼란에서 비롯되는 부정적 감정과 스트레스에 대해 보다 효과적으로 대응할 수 있게 된 것으로 보인다. 무엇보다도 단기 해외 체류 중 이 훈련이 없었으면 주의를 기울이지 않았을 세밀한 문화 차이에 대해 관심을 가지게 되었으며, 그 결과 외국인과 유대감을 갖는데 도움을 받았다고 보고하고 있다. 마지막으로, 위기사건을 활용한 결과, 학생들은 막연하게 추상적인 문화 차이에 대해 이야기하기보다, 구체적으로 어떤 행동으로 문화 차이가 나타나는지에 대해 이야기하며 이의 해석과 행동 전략 수립을 위한 추가 정보를 얻고자 하는 동기가 강해졌다. This study assumes that intercultural competency can be effectively improved by intercultural training program with the following intercultural encounters in short-term stay abroad. The purpose of the study is to develop a intercultural training program utilizing 'critical incidents' for Korean participants of short-term experiential learning program in some selected Asian countries. Those students who are going to participate in experiential learning abroad program, are likely to be fully motivated to learn, be ready to take 'mindful learning' which makes the intercultual learning more effective. Critical incidents method for intercultural training is used to make the learning more effective and the exposure to different cultures more fruitful, while helping the students get ready to solve problems, manage cultural shock and stresses in the following intercultural encounters. We developed 127 episodes of critical incidents for Korean students going to stay in 7 Asian countries, and designed 3-hour training program utilizing the critical incidents. The representative features of the 3-hour training program is identified as follows: Problem-based learning is combined with critical incidents method for intercultural training. Culture-specific approach is combined with culture-universal approach. The training program was applied to Seoul Women's University students who were to participate in a experiential learning abroad program. We came into the conclusion that the program is well designed enough to encourage the students to learn and understand cultural differences, and behave more effectively and appropriately in different cultures. KCI Citation Count: 0